Green Accounting Practice of Nipah (palm trees) Farmers Along Moncongloe Lappara Riverbanks - Nurmiati Nurmiati; Muh Rum; Murtiadi Awaluddin; Andi Sylvana (Integrated Journal of Business and Economics (IJBE), 2022)
This study aims to implement practical management accounting on nipah water by looking for inputs and outputs for other commodities. The main problem in this study is how accounting can raise environmental problems in the form of green accounting practices. The review is seen from management accounting to determine cross production between nipah water production as capital input for other commodities. Environmental accounting practices dealing with the problem of pricing agricultural products become increasingly complex in agricultural locations. The data source is primary data taken directly from 30 nipah farmers located on the banks of the Moncongloe Lappara River, Moncongloe District, Maros Regency, South Sulawesi during 2020. The analytical method used is to measure input-output commodities with the Social Accounting Matrix. The results of this study indicate that the total contribution index of sap water production from Nipah is 456.66 to other commodities, while commodity B is 1236.04 and commodity C is 851.66. With this contribution, farmers can manage their own sources of funds sourced from nipa palm water in a sustainable manner, not only farmers in the Lappara Moncongloe River area, but also the condition of nipa palm farmers in other parts of Indonesia